“The Body that Crumbled”: Mizrahi Men and the Writing of Poetic Anatomy - Tsoffar, Ruth (Hagar: Studies in Society and Culture, 2003)
This article, the first of two, studies the multiple ways in which the human body participates in the wider political project called “ethnicity, ” as a locus of its invented and received cultural meaning. In particular, the poetry of Mizrahi writers such as Erez Bitton, Roni Somek, Eli Bachar, and Peretz-Dror Banai (Israelis of Middle Eastern, North African origin) makes a strong case for a quantitative analysis of body references, frequently evoked in the poems, alluding to a specific posture and bodily situation. Once I sketched a collective body of this poetic anatomy, I identified specific issues of fragmentation, particularization and dismemberment; exploring the ability of poetic language to articulate cultural differences, textual resistance, internalized violence, or selfidentification. The fact that male and female poets construct dramatically different bodily models demanded that I discuss each of them independently in two separate articles.